The Added Benefit of Bicycle Commuting on the Regular Amount of Physical Activity Performed - Donaire-Gonzalez,D; de,Nazelle A; Cole-Hunter,T; Curto,A; Rodriguez,DA; Mendez,MA; Garcia-Aymerich,J; Basagana,X; Ambros,A; Jerrett,M; Nieuwenhuijsen,MJ (American Journal of Preventive Medicine, 2015)
IntroductionPhysical inactivity is a leading cause of death and disability globally. Active transportation such as bicycling may increase physical activity levels. It is currently uncertain whether a shift from motorized transport modes to bicycle commuting leads to increased physical activity overall or substitutes other forms of physical activity. The study aims to disentangle whether bicycle commuting adds to or replaces other physical activities by comparing the physical activity performed by bicycle and motorized commuters.MethodsPhysical activity, travel behavior, health status, sociodemographic, and built environment characteristics were assessed for 752 adults, between June 2011 and May 2012, in Barcelona, Spain. Statistical analyses, performed in 2013–2014, included linear, non-linear, and mixture models to estimate disparities and the dose–response relationship between physical activity duration and commute mode.ResultsRegular bicycle commuters traveled by bicycle an average of 3.1 (SD=2.5) hours in the previous week. Bicycle commuting contributed positively to physical activity duration across participants (p<0.05). It amounted to 2.1 (95% CI=0.84, 3.55) hours/week extra of physical activity for bicycle commuters versus motorized commuters. Among bicycle travelers, there was a positive dose–response relationship between bicycle commuting and physical activity duration, with an average extra physical activity duration of 0.5 (95% CI=0.4, 0.6) hours/week for every additional 1 hour/week of bicycle commuting.ConclusionsBicycle commuting likely adds to overall physical activity. The extra physical activity performed by bicycle commuters is undertaken as moderate physical activity and follows a sigmoidal dose–response relationship with bicycle duration.